Balancing infinity and finitude in postsocialist China on Yan Lianke's problematization of matter - Teh, Jeffrey Alester T. (College of Arts and Letters, University of the Philippines Diliman, 2017)
This study explores how Chinese novelist Yan Lianke (b.1958) represents relations between human and nonhuman actors in post-Mao China, thus articulating a conception of matter that can be properly described as postsocialist. This postsocialist conception of matter stands as a response to the dialectical materialism that dominated the Maoist era of Chinese high socialism. And, where Mao Zedong's vision of dialectical materialism claimed to produce a scientific conflation between infinity and materiality, socialist rationality and thingly plenitude, Yan complicates this formulation, interrogates it through a reckoning with material finitude. What emerges from such an encounter, though, it is not a simplistic rejection of infinity, certainly not a triumphalist dismissal of the socialist promise of material abundance. Rather, the postsocialist conception of matter is more so a recognition that matter itself is caught between infinity and finitude, transcendence and cynicism. An ambiguous picture arises, overall - tense, conflicted, and uncertain.